Answer:
5
Step-by-step explanation:
Let's just pretend the 6 numbers are: a,b,c,d,e,f.
Then (a+b+c+d+e+f)/6 =4 (given by first statement.)
Let's pretend the average of 2 numbers is 2 means they are talking about the a and b.
So (a+b)/2=2.
Now we want to find (c+d+e+f)/4 as requested by their question.
So first step multiply both sides of our first equation by 6 giving us:
a+b+c+d+e+f=24
So the second step multiply both sides of our second equation by 2 giving us:
a+b=4.
Now if a+b+c+d+e+f=24 and a+b=4, then c+d+e+f=20 since 20+4=24.
So the average of the four numbers c,d,e, and f is 20/4=5.